Surplus Masculinities and Security - Cowen, Deborah; Siciliano, Amy (Antipode, 2011)
:  In this paper we investigate geographies of military recruitment and urban policing as key domains for both the management of surplus populations and the extraction of surplus value. Drawing on research in North America and the UK, we explore the emerging institutions, social technologies, and political economies that constitute a racialized and gendered geography of what we term “securitized social reproduction”. We suggest that so‐called “redundant” populations of underemployed racialized men are at the centre of contemporary politics of security. We explore the increasingly productive role of surplus populations in security industries, and the resurgence of public masculinities that seek to both valourize and discipline subjects and populations. This resurgence of masculinity is taking shape through both the expansion of security industries and the entanglement of police and military force. This paper suggests that a focus on ‘surplus’ highlights the geographies and profits at stake in securing social reproduction.